Antibodies against HDL Components in Ischaemic Stroke and Coronary Artery Disease - Batuca, Joana R.; Amaral, Marta C.; Favas, Catarina; Justino, Gonçalo C.; Papoila, Ana L.; Ames, Paul R. J.; Alves, José Delgado (Thrombosis and Haemostasis, 2018)
Quantitative and qualitative defects of high-density lipoprotein (HDL) are important in atherogenesis. In this study, we investigated whether antibodies against HDL components had additional value to conventional cardiovascular risk factors for the diagnosis of ischaemic stroke (IS) and coronary artery disease (CAD). Cross-sectional study was conducted on 53 patients with IS, 51 with CAD and 55 healthy controls, and in vitro studies to validate findings of the clinical study. We determined serum immunoglobulin G (IgG) antibodies against HDL (aHDL), apolipoproteins (aApoA-I, aApoA-II and aApoC-I) and paraoxonase-1 (aPON1) as well as PON1 activity (PON1a), total antioxidant capacity and biomarkers of endothelial activation (serum nitric oxide metabolites, 3-nitrotyrosine, VCAM-1 and ICAM-1); in vitro assays tested the capacity of IgG aHDL purified from high titer patients to inhibit PON1a and to reverse protective effect of HDL on endothelial cells. IgG aHDL, aApoA-I and aPON1 were higher in IS and CAD than controls (p < 0.001), predicted negatively PON1a and positively VCAM-1 and ICAM-1. By adding IgG aHDL and aApoA-I to a traditional cardiovascular risk factors model for IS and by adding IgG aHDL in a similar model for CAD, we obtained better discrimination of IS and CAD from healthy controls. IgG aHDL purified from IS and CAD inhibited PON1a by 38% (p < 0.01) and abrogated the protective effect of HDL on VCAM-1 expression by 126% compared with non-specific human IgG (p < 0.001). IgG against HDL components interfere with the antioxidant and anti-inflammatory properties of HDL and may represent novel biomarkers for vascular disease that need to be investigated in prospective studies.
Keywords: high-density lipoprotein; auto-antibodies; coronary artery disease; ischaemic stroke; HDL dysfunction